Twin‐twin transfusion syndrome complicated by single ventricle physiology: A case report. Issue 11 (20th August 2021) - Kiss, Edgar; Chehab, Sarah; Moreno Duarte, Ingrid; Khan, Umar; Schindel, David; Pandya, Samir; Ullah, Sana; Ochoa, Courtney; Zabala, Luis M.
Abstract: Clinically significant extrauterine twin‐twin transfusion syndrome in conjoined twins is rare and carries a high risk of perinatal mortality. The ensuing postnatal imbalance in circulation across connecting vessels results in hypovolemia in the donor and hypervolemia in the recipient. Data on management and treatment are sparse especially in the setting of a single ventricle congenital heart defect. We present a case of a pair of omphalopagus conjoined twins, one with a single ventricle physiology (Twin B), who developed twin‐twin transfusion syndrome shortly after birth. The resulting pathophysiology in the setting of a single ventricle congenital heart defect created added layers of complexity to their management and expedited surgical separation. Shunting from Twin B to Twin A—with an anatomically normal heart—resulted in mal‐perfusion and rapid deterioration jeopardizing the health of both twins. In the preoperative course, steps taken to medically optimize the twins prior to surgery and the anesthetic considerations are detailed in this report.